ANALISIS APLIKASI BELAJAR JAM DAN WAKTU PADA TEMA KESELAMATAN DIRUMAH DAN PERJALANAN (Penelitian Eksperimen Pada Siswa Kelas 2 Sekolah Dasar) - Murdani, Dani; Hendriawan, Deri (Didaktika, 2022)
The background of this research was the researcher's interest in finding out about an application called the Clock and Time Learning application to be used as a learning medium in elementary schools, especially in mathematics subjects. The research method used in this research is the experimental method. The subjects of this study were grade II students of the State of Elementary School of Mongpok 1. This study has limitations on respondents due to the Covid-19 pandemic, in accordance with restriction regulations during covid. In this study, researchers experimented with whether the Clock and Time Learning application could be an appropriate learning medium for teaching second grade elementary school students how to read clocks and time correctly and in fun. The results of this research from the test results show that 90% of students were able to achieve the learning objectives in terms of knowledge with an average score of 70. Based on this average score, only one student out of 10 students who took the test got a score below the average. This shows that the Clock and Time Learning application can help students learn to read clocks and time, because this application is presented in animated form and is also accompanied by sounds that can make students more enthusiastic about learning. In conclusion, the Clock and Time Learning application can be used as a learning medium in the learning process for teachers, parents and students.